2004
DOI: 10.1002/bit.20330
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence and CD spectroscopic analysis of the α‐chymotrypsin stabilization by the ionic liquid, 1‐ethyl‐3‐methylimidazolium bis[(trifluoromethyl)sulfonyl]amide

Abstract: The stability of alpha-chymotrypsin in the ionic liquid, 1-ethyl-3-methyl-imidizolium bis[(trifluoromethyl)sulfonyl]amide ([emim][NTf2]), was studied at 30 and 50 degrees C and compared with the stability in other liquid media, such as water, 3 M sorbitol, and 1-propanol. The kinetic analysis of the enzyme stability pointed to the clear denaturative effect of 1-propanol, while both 3M sorbitol and [emim][NTf2] displayed a strong stabilizing power. For the first time, it is shown that enzyme stabilization by io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
139
2
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 190 publications
(169 citation statements)
references
References 31 publications
24
139
2
4
Order By: Relevance
“…Recent spectroscopic studies of protein thermostability in ILs have indicated that the significant thermodynamic stabilization effect offered by the ionic liquid seemed to be related to the structural changes of the protein: 31 -33 The fluorescence spectra clearly showed the ability of the ILs to compact the native structural conformation of the enzyme, preventing the usual thermal unfolding which occurs in other media. 31,32 The circular dichroism (CD) spectra also demonstrated changes in the secondary structure of the protein in the presence of the ILs, resulting in a more compact enzyme conformation able to exhibit catalytic activity. 32,33 Moreover, differential scanning calorimetry (DSC) revealed that both the melting temperature and heat capacity of the enzyme were enhanced in the presence of ILs as compared with the other media.…”
Section: Thermal Stability Of Enzymementioning
confidence: 99%
See 2 more Smart Citations
“…Recent spectroscopic studies of protein thermostability in ILs have indicated that the significant thermodynamic stabilization effect offered by the ionic liquid seemed to be related to the structural changes of the protein: 31 -33 The fluorescence spectra clearly showed the ability of the ILs to compact the native structural conformation of the enzyme, preventing the usual thermal unfolding which occurs in other media. 31,32 The circular dichroism (CD) spectra also demonstrated changes in the secondary structure of the protein in the presence of the ILs, resulting in a more compact enzyme conformation able to exhibit catalytic activity. 32,33 Moreover, differential scanning calorimetry (DSC) revealed that both the melting temperature and heat capacity of the enzyme were enhanced in the presence of ILs as compared with the other media.…”
Section: Thermal Stability Of Enzymementioning
confidence: 99%
“…31,32 The circular dichroism (CD) spectra also demonstrated changes in the secondary structure of the protein in the presence of the ILs, resulting in a more compact enzyme conformation able to exhibit catalytic activity. 32,33 Moreover, differential scanning calorimetry (DSC) revealed that both the melting temperature and heat capacity of the enzyme were enhanced in the presence of ILs as compared with the other media. 32 Thus, the observable improvement in the stability of Novozym 435 in ILs is most probably due to the electrostatic interaction between the ILs and the protein, leading to a more rigid protein, which needs to overcome a higher kinetic barrier to unfold in comparison with the cases when the enzyme is incubated in organic solvents.…”
Section: Thermal Stability Of Enzymementioning
confidence: 99%
See 1 more Smart Citation
“…Although traditional ionic liquids are frequently synthesized from imidazolium-based cations and highly fluorinated anions, recent work has shown that ionic liquids can also be formulated from salts (Abbott et al, 2001), sugars (Carter et al, 2004), amino acids (Fukumoto et al, 2005;Tao et al, 2005), and biomolecules (Pernak et al, 2004) that exist in nature, many of which have already been approved as pharmaceutical excipients. Previous work in recent years has shown that enzymes and some proteins can be active in ionic liquids; however, structure is disrupted in many cases (Diego et al, 2004;Laszlo and Compton, 2002;Lau et al, 2004). In a recent report a new family of biocompatible ionic liquids based on the dihydrogen phosphate anion were described (Fujita et al, 2005); these ILs were able to dissolve substantial quantities of cytochrome c (cyt c) and in the solution the protein was shown to retain its structure and activity.…”
Section: Introductionmentioning
confidence: 99%
“…They are used for the synthesis of aliphatic and aromatic esters, chiral esters by kinetic resolution of racemic alcohols, carbohydrate esters, polymers, etc. Additionally, the excellent stability displayed by enzymes in water-immiscible ILs for reuse and under high temperatures has been widely described [45]. Concerning medium engineering for biotransformations in ILs, it has been reported that ILs improves activity (e.g.…”
Section: Fig (5)mentioning
confidence: 99%